Airway management in microgravity: a systematic review - Warnecke, Tobias; Neuhaus, Christopher (Acta anaesthesiologica Scandinavica, 2019)
Introduction In the near future, space programs will shift their focus toward long-duration interplanetary missions, in particular to the Moon and Mars. These exploration missions will be associated with an increased risk of acute medical problems, which will need to be handled by an autonomous crew operating in extreme isolation. An important skill in emergencies is represented by airway management. Many airway devices are available and it is unclear which one would be the most suitable in the context of a space mission. The aim of this systematic review was to analyze the existing literature on airway management in the special situation of weightlessness during space missions. Material and methods We performed a standardized review of published literature on airway management in spaceflight and analogue environments using the database PubMed. Results We identified a total of 3111 publications of which 3039 were initially excluded after evaluation. The screening identified three randomized comparative manikin studies, two of them in parabolic flights, one in a submerged setup. Under free-floating conditions, the insertion success rate of supraglottic airway devices (SGA) was excellent (91%-97%). The administration of artificial ventilation could be successfully achieved in weightlessness with SGA. The success rate of conventional laryngoscopy under free-floating conditions fluctuated between 15% and 86%. Conclusion It appears possible to safely manage the airway in weightlessness, provided that certain conditions are ensured, such as restraining the patient and operator for conventional orotracheal intubation. If airway protection is required with endotracheal intubation, both the operator and the patient should be restrained.
First published: 10 September 2018
Gesehen am 29.07.2019